Advancing microfluidic single-cell analysis technologies, techniques, and applications for the study of cancers and neuroinflammatory diseases - Sibbitts, Jay (Kansas State University, 2020)
As the fight against cancers, neuroinflammatory diseases, and other chronic illnesses progresses, bioanalytical technologies and techniques must also advance to provide researchers with a greater depth of information so they may better understand what factors are at play at the cellular level. In recent years, researchers have begun to turn toward the rapidly growing field of microfluidics. Microfluidic technologies have proven to be invaluable in a wide variety of bioanalytical applications in areas such as point-of-care diagnostics, in vitro cellular analysis, and especially single-cell analysis. The chapters of this dissertation will present and discuss results and progress on 3 microfluidic-based projects. Chapter 2 reports improvements made on the single-cell analysis (SCA) system developed by the Culbertson group that were enabled by low-cost electronics and 3D printing technology. Additionally, results of the measurement of intracellular nitric oxide (NO), an inflammatory biomarker, in single cells using a model cell line (Jurkat, T-lymphocytes) under inflammatory, native, and inhibitory conditions are reported. Chapter 3 incorporates the improvements described in Chapter 2 and demonstrates the capabilities of the SCA system for applications in studying the effects of anti-inflammatory therapeutics for the treatment of neurodegenerative pathologies. An analytical strategy, similar to that developed in Chapter 2, is used to measure intracellular NO levels in the recently discovered immortalized SIM-A9 microglia cell line. Additionally, Chapter 3 presents an interesting in-depth statistical analysis on the distributions of NO levels in microglia under inflammatory, native, and inhibitory conditions, which highlights the potential depth of information made available by performing analyses with single-cell resolution. Finally, Chapter 4 will focus on efforts toward developing a solid-state actuation modality using a dielectric elastomer. The ultimate goal for the dielectric elastomer actuator technology will be to perform 2 functions in microfluidic systems: the application of precise mechanical stress on cells to study potentially interesting mechanotransduction phenomena and to serve as the basis for a novel non-pneumatic valve.
Keywords: Microfluidics; Inflammation; Electrophoresis